Bulk Viscous Bianchi Type-V Cosmological Model in f(R, T) Theory of Gravity - Brahma, Bishnu Prasad; Dewri, Mukunda (Frontiers in Astronomy and Space Sciences, 2022)
This paper deals with the bulk viscous Bianchi type-V cosmological model with exponential scale factor in Lyra geometry based on $f(R,T)$ gravity, by considering a time dependent displacement field. To determine the nature and physical properties of the model, we considered Harko et al.\cite{Harko2011} [proposed the linear form $f(R,T)=f_{1}(R)+f_{2}(T)$], in which the barotropic equation of state for pressure, density, and bulk viscous pressure is proportional to energy density. The kinematical properties of the model is also discussed in presence of bulk viscosity. Evolution of energy conditions is also studied and examined the behaviour of that in order to explain the late-time cosmic acceleration.